Command of Jihad through Devotion to Parents According to Hadith - Darmalaksana, Wahyudin; Shofiyatus Salamah, Nyimas Shoffah (International Journal of Islamic Khazanah, 2022)
The purpose of this research is to discuss the commandment to filial piety to parents in the hadith. This research method uses a qualitative type through literature study by applying content analysis. The discussion of this research includes the meaning of filial piety to parents, the hadith of the commandment of filial piety to parents, and the obligation of children’s behavior to parents. This research concludes that filial piety in the sense of respecting parents is an obligation in Islam, the command to filial piety according to the hadith is understood as jihad, and behavior towards parents includes when the parents are still alive and when they have died. This research is expected to have benefits for the enrichment of Islamic knowledge.